Quantitative Analysis of Hydrochlorothiazide Tablets Using Lignocaine Hydrochloride as Hydrotropic Agent - Maheshwari, R.K.; Deswal, S.; Tiwari, D.; Ali, N.; Jain, S. (Asian Journal of Chemistry, 2010)
There was more than 50-fold enhancement in aqueous solubility of hydrochlorothiazide in 1 M lignocaine hydrochloride solution as compared to the solubility in distilled water. Therefore 1 M lignocaine hydrochloride solution was employed to extract out the drug from fine powder of the tablets of hydrochlorothiazide to carry out spectrophotometric estimation at 317 nm (selected wavelength). The hydrotropic agent and the additives used in the manufacture of tablets did not interfere in the analysis. Statistical data proved the accuracy, reproducibility and precision of proposed method.